The Comparison of Chosen - Bonded with the Use of Classical and Dedicated for 3D Printing Furfuryl Binder - Molding Sands’ Properties as a Basis for Development a New Inorganic System - D.M. Halejcio; K.A. Major-Gabryś (Archives of Foundry Engineering)
Binder jetting technology (3D printing) in the production of foundry molds and cores is becoming more and more industrially used due to ensuring very good quality of the casting surface. In 3D printing technology as the matrix, quartz sand is mainly used, with a grain size of 0.14-0.25 mm. The binder is an organic binder - most often furfuryl resins. As part of this work, self-hardening molding sands with furfuryl resins dedicated to the classic production of molds and cores, as well as molding sands with resin dedicated to 3D printing, were tested. The aim of the research was to compare the viscosity of binders and the properties of molding sands prepared based on binding systems both dedicated to the classic production of molds and cores and for 3D printing. Tests were carried out on the binding kinetics, bench life, strength properties, permeability, abrasion and hot distortion of molding sands prepared on the basis of a standard medium grain matrix and sieved fine-grain matrix. The carried-out tests have shown that the binding system based on furfuryl resin elaborated for 3D printing of molding sands provides strength properties of the sands similar to the classic system of binding self-hardening molding sands with furfuryl resins. However, it ensures faster binding speed and greater thermal stability measured by the hot distortion parameter. The use of a fine-grained matrix results in a decrease in the strength properties of all the molding sands. On the basis of the results achieved for molding sands with organic binding system, a new inorganic binding system was elaborated.